Climate analysis for noise assessment. (April 2017) - Swearingen, Michelle E.; Horvath, Rachael; White, Michael J.
Abstract: Long-term noise assessments are performed as part of the National Environmental Policy Act (NEPA) process prior to construction of facilities or significant changes to operations on military installations. In the past, these assessments have been based on a single, typical or average propagation condition. ISO 13474 dictates that a weighted set of propagation condition-specific tables shall be used within the noise assessment. In this paper we explore the differences between noise assessments using local conditions and the averaged condition. We found that the assessed annual C-weighted sound exposure level (CSEL) using conditions for seven geographically different locations differed by up to 3 dB in the four cardinal directions for distances up to 10 km, indicating that an average propagation condition may be satisfactory for most locations.